2012
DOI: 10.1021/ol300058t
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)-Cyperolone

Abstract: The total synthesis of (+)-cyperolone, an eudesmane-derived sesquiterpenoid from Cyperus rotundus, is described. The de novo synthesis was accomplished via a 15 step sequence starting from (R)-(-)-carvone. The synthetic route features a platinum-catalyzed cycloisomerization to rapidly construct the bicyclic core from a 3-silyloxy-1,5-enyne intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…They were successfully used for the total synthesis of natural products, which included Brasilicardins A and C, (+)‐Frondosin A, (+)‐Tanikolide, Lundurines A−C, Onoseriolid, Isobolivianine, (−)‐Crinipellin A, Panaginsene, Echinopines, (+)‐ and (−)‐Isolaurepan, (−)‐Strychnofoline, (−)‐Clovan‐2,9‐dione, (+)‐Sarcophytin, [2 ° ] (+)‐Chatancin, [2 ° ] (−)‐3‐Oxochatancin, [2 ° ] (+)‐Cyperolone . In these cases, TsNHNH 2 reacted with aldehydes (or ketones) to form hydrazones that underwent cycloaddition or reduction subsequently. Banford‐Stevens reaction and Shapiro reaction were reported in this decade.…”
Section: Introductionmentioning
confidence: 99%
“…They were successfully used for the total synthesis of natural products, which included Brasilicardins A and C, (+)‐Frondosin A, (+)‐Tanikolide, Lundurines A−C, Onoseriolid, Isobolivianine, (−)‐Crinipellin A, Panaginsene, Echinopines, (+)‐ and (−)‐Isolaurepan, (−)‐Strychnofoline, (−)‐Clovan‐2,9‐dione, (+)‐Sarcophytin, [2 ° ] (+)‐Chatancin, [2 ° ] (−)‐3‐Oxochatancin, [2 ° ] (+)‐Cyperolone . In these cases, TsNHNH 2 reacted with aldehydes (or ketones) to form hydrazones that underwent cycloaddition or reduction subsequently. Banford‐Stevens reaction and Shapiro reaction were reported in this decade.…”
Section: Introductionmentioning
confidence: 99%
“…3) . This cyclization strategy was the key step of the total synthesis of (+)‐cyperolone, although in this particular case platinum(IV)chloride was superior to gold catalysts . Kirsch, Rhee and co‐workers also studied the analogous reactivity 3‐silyloxy‐1,6‐enynes in the presence of gold catalysts .…”
Section: 2‐alkyl Migrationmentioning
confidence: 99%
“…[19] This cyclization strategy was the key step of the total synthesis of (+)-cyperolone, although in this particular case platinum(IV)chloride was superior to gold catalysts. [20] Kirsch, Rhee and co-workers also studied the analogous reactivity 3-silyloxy-1,6-enynes in the presence of gold catalysts. [21] The 1,6-enynes may react through two different pathways: i) 6-exo carbocyclization followed by pinacol rearrangement or ii) heterocyclization followed by Claisen rearrangement.…”
Section: 2-alkyl Migrationmentioning
confidence: 99%
“…55 Using this method as the key step, Kirsch and coworkers finished the total synthesis of (þ)-cyperolone (Scheme 45). 56 For 3-silyloxy-1,6-enyne compound, the corresponding tandem process will start with a 6-exo-dig cyclization of the alkene moiety with gold(I) catalyst. 57 It has been found that the electronic property of the phosphine ligand affects the selectivity of this transformation significantly.…”
Section: Other Tandem Versionmentioning
confidence: 99%